A Large Animal Model for Orthopedic Foot and Ankle Research - Gadomski, Benjamin C.; Labus, Kevin M.; Stewart, Holly L.; Bisazza, Katie T.; Nelson, Brad B.; Puttlitz, Christian M.; McGilvray, Kirk C.; Regan, Daniel P.; Easley, Jeremiah T. (Frontiers in Veterinary Science, 2022)
Trauma to the soft tissues of the ankle joint distal syndesmosis often leads to syndesmotic instability, resulting in undesired movement of the talus, abnormal pressure distributions, and ultimately arthritis if deterioration progresses without treatment. Historically, syndesmotic injuries have been repaired by placing a screw across the distal syndesmosis to provide rigid fixation to facilitate ligament repair. While rigid syndesmotic screw fixation immobilizes the ligamentous injury between the tibia and fibula to promote healing, the same screws inhibit normal physiologic movement and dorsiflexion. It has been shown that intact screw removal can be beneficial for long-term patient success; however, the exact timing remains an unanswered question that necessitates further investigation, perhaps using animal models. Because of this sparsity of relevant preclinical models, the purpose of this study was to develop a new, more translatable, large animal model that can be used for the investigation of clinical foot and ankle implants. Eight (8) skeletally mature sheep underwent stabilization of the left and right distal carpal bones following transection of the dorsal and interosseous ligaments while the remaining two animals served as un-instrumented controls. Four of the surgically stabilized animals were sacrificed six weeks after surgery while the remaining four animals were sacrificed 10 weeks after surgery. Ligamentous healing was evaluated using radiography, histology, histomorphometry, and histopathology. Overall, animals demonstrated a high tolerance to the surgical procedure with minimal complications. Animals sacrificed at 10 weeks post-surgery had a slight trend towards mildly decreased inflammation, decreased necrotic debris, and a slight increase in the healing of the transected ligaments. The overall degree of soft tissue fibrosis/fibrous expansion, including along the dorsal periosteal surfaces/joint capsule of the carpal bones was very similar between both timepoints and often exhibited signs of healing. The findings of this study indicate that the carpometacarpal joint may serve as a viable location for the investigation of human foot and ankle orthopaedic devices. Future work may include the investigation of orthopaedic foot and ankle medical devices, biologic treatments, and repair techniques in a large animal model capable of providing translational results for human treatment.